0036 Development of a high fidelity oncoplastic breast simulation model. (2nd November 2015) - Willers, Johann; Bonomi, Ricardo; Rapisarda, Fabio; Betal, Dibendu
Abstract : Background: Cosmetic reconstruction during surgery for carcinoma of the breast is the procedure preferred by patients. This means that the tumour removal is approached like a combination breast reduction and lift, followed by a similar procedure on the other side ensuring symmetry. 1 This oncoplastic surgery requires the utmost precision, and it would be helpful if high fidelity simulation training for this procedure could done, but unfortunately this has not been possible up to now. After handling and cutting ADAMgel (A queous D ietary fibre A ntifreeze M ix gel) breast biopsy phantoms the oncoplastic surgeons at our establishment wondered if it would be possible to use this material to develop a model to supply this need. Method: A breast simulacrum was manufactured from concentric layers of ADAMgel by pouring it while hot into stockinette (representing dermis, Scarpa's Fascia and Cooper's ligaments), and the covered in a nylon stocking impregnated with ADAMgel (epidermis analogue). The bottom end was fashioned into a nipple then the construct was suspended to cool allowing gravity to give it the correct shape. Result: The resulting breast phantom had the correct consistency and texture under hand and scalpel, could be dissected and sutured like real breast tissue. The soft ADAMgel breast tissue was restrained and supported by the fascial analogues (stockinette), allowing shape change by handling and gravity, emulating human anatomy. Diathermy can be used and models can be prepared in various shapes and sizes, and at differing consistencies. The total cost of the first phantom was <£3, but subsequently cheaper as the ADAMgel can be reused. Conclusion: The development of this realistic breast model will make affordable oncoplastic high-fidelity surgical simulation feasible for the first time. The low cost will allow these very valuable skills to be nurtured, to the benefit of the many patients with this common cancer. Reference: Chang M, Huston T, Ascherman J, Rohde C. Oncoplastic breast reduction: maximizing aesthetics and surgical margins. Int J Surg Oncol 2012:907576J